New Design Scheme for and Application of Fresnel Lens for Broadband Photonics Terahertz Communication - Peng Tian; Yang Han; Weiping Li; Xiongwei Yang; Mingxu Wang; Jianjun Yu (Sensors)
In terahertz communication systems, lens antennas used in transceivers are basically plano-convex dielectric lenses. The size of a plano-convex lens increases as the aperture increases, and thinner lenses have longer focal lengths. Through theory and simulation, we designed a Fresnel lens suitable for the terahertz band to meet the requirements of large aperture and short focal length, and simulated the performance, advantages, and disadvantages of the terahertz Fresnel lens. A 300 GHz terahertz wireless communication system was built to verify the gain effect of the Fresnel lens antenna. The experimental results demonstrate that the Fresnel lens can be used for long-distance terahertz communication with larger aperture diameters, overcoming the limitations of traditional plano-convex lenses. The theoretical gain of a 30 cm Fresnel lens is 48.83 dB, while the actual measured gain is approximately 45 dB.